Human Computer Interface for Tracking Eye Movements Improves Assessment and Diagnosis of Patients With Acquired Brain Injuries - Lech, Michał; Kucewicz, Michał T.; Czyżewski, Andrzej (Frontiers in Neurology, 2019)
One of the first clinical signs differentiating the minimally conscious state from the vegetative state is the presence of smooth pursuit eye movements occurring in direct response to moving salient stimuli. Glasgow Coma Scale (GSC) is one of the most commonly used diagnostic tools to assess the level of consciousness. However, GSC is limited to standard neurological examination without tracking position of the gaze. Among this and other limitations, it is prone to a relatively high rate of misdiagnosis. Here, we developed an interface for gaze tracking to enhance the assessment of consciousness in 10 patients with acquired brain injuries. According to the GSC assessment, 9 of them were considered unaware and below the minimally conscious state (GCS ≤ 8). Our new Human Computer Interface (HCI) revealed that 6 of them were conscious enough to complete at least one of the gaze tracking tasks. Among these 6 patients, one was originally diagnosed as remaining in a persistent vegetative state and one in coma. The patient in a persistent vegetative state scored 6 GCS points, which suggested an absolute lack of awareness. Following assessment with our HCI the patient was re-diagnosed with a possible locked-in syndrome. Our HCI method provides a new complementary tool for clinical assessment of patients suffering from disorders of consciousness.